Implementation of Islamic Religious Education Values in the Book of Ta'lim Muta'allim - Yanto, Lutfi; Yaqin, Muhammad Nurul (Program Pascasarjana UIN Sumatera Utara, 2024)
This research examines how the values of Islamic religious education in the book Ta'lim Muta'allim are applied in class I MTs and what are the supporting and inhibiting factors in the application of Islamic religious education values in the book Ta'lim Muta'alim in class I MTs. The book Ta'lim Muta'allim discusses learning procedures and moral attitudes in learning that students must have. This research uses descriptive qualitative methods. Data collection techniques include interviews, observation, and documentation, while data analysis techniques include data reduction, data presentation, and data verification. As an instrument, the researcher chose the MTs principal, Ta'lim Muta'allim teacher and MTs class I students. Data collection techniques include interviews, observation, and documentation. The data analysis techniques include data reduction, data presentation and verification. Forms of applying the values of Islamic religious education in the book Ta'lim Muta'allim in class I MTs include: First, reading surah Yasin and Al-luqman, second, studying the book Ta'lim Muta'allim in groups, Third, performing prayers dhuha sunnah and midday prayers in congregation. Fourth, actively participate in activities that promote the values of Islamic religious education in the surrounding community, such as inviting other people to pray in the congregation or helping people in need. Supporting factors for implementing the values of Islamic religious education in the book of ta'lim muta'allim in class I MTs include the availability of adequate facilities and infrastructure, the presence of resident students and the presence of teachers who have basic huts. Inhibiting factors in implementing the values of Islamic religious education in the ta'lim muta'alim book in class I MTs include the presence of non-resident students, differences in character and the presence of apathetic parents.Penelitian ini mengkaji bagaimana penerapan nilai-nilai pendidikan agama Islam dalam kitab Ta'lim Muta'allim di kelas I MTs dan Apa saja faktor pendukung dan penghambat dalam penerapan nilai nilai pendidikan agama Islam dalam kitab Ta’lim Muta’alim di kelas I MTs. Kitab Ta'lim Muta'allim membahas tentang tata cara belajar dan sikap moralitas dalam belajar yang harus dimiliki oleh siswa tersebut. Penelitian ini menggunakan metode kualitatif deskriptif. Teknik pengumpulan data meliputi wawancara, observasi dan dokumentasi, sedangkan teknik analisis data meliputi reduksi data, penyajian data dan verifikasi data. Peneliti sebagai instrument memilih kepala sekolah MTs, guru pengajar Ta’lim Muta’allim dan siswa kelas I MTs. Teknik pengumpulan data meliputi wawancara, observasi dan dokumentasi. Adapun teknik analisi data meliputi reduksi data, penyajian data dan verifikasi. Bentuk penerapan nilai-nilai pendidikan agama Islam dalam kitab Ta'lim Muta'allim di kelas I MTs di antaranya: Pertama, membaca surah Yasin dan Al-luqman, kedua, mempelajari kitab Ta'lim Muta'allim secara berkelompok, Ketiga, melaksakan shalat sunah dhuha dan sholat dhuhur berjamaah, Keempat, berpartisipasi aktif dalam kegiatan-kegiatan yang mempromosikan nilai-nilai pendidikan agama Islam di masyarakat sekitar, seperti mengajak orang lain untuk shalat berjamaah atau membantu orang yang membutuhkan. Faktor pendukung penerapan nilai nilai pendidikan agama Islam dalam kitab ta’lim muta’allim di kelas I MTs diantaranya: tersedianya sarana dan prasarana yang memadai, adanya siswa mukim dan adanya guru-guru yang memiliki basik pondok. Faktor penghambat dalam penerapan nilai nilai pendidikan agama Islam dalam kitab ta’lim muta’alim di kelas I MTs diantaranya: adanya siswa non mukim, adanya perbedaan karakter dan adanya orang tua yang apatis.